Nangun Sad Kertih Oriented Heutagogy Approach in Social Studies Learning and Its Impact on Social Care Attitudes and Digital Skills - I Wayan Kertih; I Putu Sriartha (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
This study aims to analyze the impact of Nangun Sad Kertih's oriented heutagogy approach in IPS on social care attitudes and digital skills. This study is quasi-experimental with a nonequivalent post-test-only control group design. This study was conducted with a population of 150 grade VIII students of SMP Lab Undiksha Singaraja. The technique used to take samples is a random sampling technique. Based on random sampling results, a sample of 63 students was obtained, divided into two classes, the experimental group and 32 students in the control group 31. Data on social care attitudes and digital skills were collected using questionnaires. This study used descriptive and inferential analysis methods. Inferential analysis was performed using multivariate (Manova), preceded by an analysis prerequisite test that included a data distribution normality test and a variance homogeneity test. The results of the hypothesis test based on the test results between the effects of the subjects obtained significant values of Nangun Sad Kert ih-oriented heutagogy approach to social care attitudes and digital skills obtained a significance value of 0.000 < 0.005, which means that the Nangun Sad Kert oriented heutagogy approach improves digital skills and social care attitudes in social studies learning. In conclusion, Nangun Sad Kert's heutagogy-based approach improves digital skills and social care attitudes.